Nursery growth performance of intact males and barrows - M M Rantanen; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 100 weanling pigs with an average initial body wt of 11.8 lb and average age of 17 d was used in a 38-d growth assay to determine the effect of castration on growth performance of nursery pigs. All pigs were fed the same Phase I, II, and III diets formulated to 1.6, 1.4, and 1.35% lysine, respectively. Data indicated no differences in growth performance between intact males and barrows in the first 38 d postweaning (12 to 48 lb).; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Starter; Performance; Boars; Barrows